Injured Adolescents, Not Just Large Children: Difference in Care and Outcome between Adult and Pediatric Trauma Centers. Issue 3 (March 2013) - Matsushima, Kazuhide; Schaefer, Eric W.; Won, Eugene J.; Nichols, Pamela A.; Frankel, Heidi L.
Adolescent injury victims receive care at adult trauma centers (ATCs) and pediatric trauma centers (PTCs). The purpose of this study was to identify care variations and their impact on the outcome of adolescent trauma patients treated at PTC versus ATC. We queried the Pennsylvania Trauma Systems Foundation database for trauma patients between 13 and 18 years of age from 2005 to 2010. Mortality and hospital complication rates between ATC and PTC were compared in univariable and multivariable analysis. In addition, the differences in the delivery of care were also compared. Of 9033 total patients, 6027 (67%) received care at an ATC. Patients in the ATC group were older (16.7 vs 14.9 years, P < 0.001) and more severely injured (Injury Severity Score: 14.5 vs 12.2, P < 0.001). Admission diagnostic computed tomography (CT), emergent laparotomy and craniotomy, blood transfusion, and drug screening were more frequently performed at an ATC. After adjustment for potential confounders in multivariable regression models, treatment at a PTC was significantly associated with fewer CTs for transferred patients (odds ratio [OR], 0.28; P < 0.001) and with less frequent emergent laparotomy for all patients (OR, 0.65; P = 0.007). The ATC group had a significantly higher hospital mortality rate (2.9 vs 0.9%, P < 0.001) and complication rate (9.7 vs 4.8%, P < 0.001). However, these outcomes were not significantly different between PTC and ATC in multivariable regression models. In the state of Pennsylvania, there were no significant differences in risk-adjusted outcomes between PTC and ATC despite significant difference in use of CT scanning and emergent laparotomy.